Enhancement on anaerobic digestion of food waste using spend coffee ground derived biochar for biogas production - Nurin Arissa, Noor Azmi; Muhammad Fahmi, Ariffin; Noor Yahida, Yahya; Siang, Lee Yong (Semarak Ilmu Publishing, 2025)
In recent, one of the available energy sources is biogas where it is suitable for necessities of the future with the appropriate application of digestion technology. However, the technology used which is anaerobic digestion (AD) faces some challenges especially for food waste including low biogas productivity due to unstable operation efficiency. In order to overcome this shortcoming, spent coffee ground (SCG) derived biochar is introduced as an additive in AD process to enhance the production. To promote the efficiency of the AD, the optimum condition of biochar dosage, the amount of feedstock and pH value were studied. The experimental findings revealed that 13.528ml/g of biogas yield was achieved under optimum condition of 7g of biochar, 500g of feedstock at pH 7 for 14 days. The characterization analysis of biochar showed that, the carbon content and surface area as well as several functional groups of SCG biochar has led to the enhancement of the biogas production during AD process of food waste. The outcomes shows that the addition of SCG biochar can solve the instability issues of AD process yet increase the production of biogas.